Socio-economic Analysis of Street Vending in Asmara city, Eritrea: Case Study Edaga-Hamus - Mihretab Ghebrezgabher; Hummed Ali (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2023)
Purpose: The purpose of this research is to examine street vending activity in Asmara city, Eritrea, including driving factors, challenges and income generated from this activity.Methodology: Data are obtained through interview and questionnaire survey from Edaga-Hamus area, and the data were processed using GeoDa software. Descriptive and inferential statistical methods are adopted to evaluate the results.Findings: The results reveal that approximately 83.3% vendors work more than 8 hours per day and 50% work for the whole week except on Sunday. Unemployment (44.44%) and family problems (37.04%) are driving factors. Moreover, there is direct relationship between income generated and level of education, business skill, and working hours. The earnings of street vendors increases very significantly with adequate educational level (p=0.00361) and with increase working hours (p=0.00003). Originality/Novelty: Study on street vending economic activity is very limited in Eritrea. Thus, it might be the first academic contribution to review the economic stiustion of steet vending activities in Eritrea.Implications: This research work will be significant for decision and policy makers to eradicate and manage street vending activity in various cities and towns of the country. In addition it will be useful for further study.